Il GIS per la gente secondo ESRI - Redazione, Redazione (GEOmedia, 2008)
ESRI's GIS people for people The eleventh edition of the local ESRI User Conference took place at the Massimo Auditorium in Rome. The event featured interesting issues, regarding the new ArcGIS version 9.3 and the unified company image. This decision symbolizes the will of ESRI US to unify the different efforts and brands of local multinational companies into a single recognizable logo.